2008
DOI: 10.1177/0891241607309476
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Family and Peer Risk Networks on Drug Use Practices and Other Risks among Mexican American Noninjecting Heroin Users

Abstract: Noninjecting heroin use (NIU) is spreading among social networks of young Mexican American polydrug users. This article examines the influence of family and peer networks on NIU behavior and other drug practices and risks. This study delineates the extent to which a culturally relevant modification of the "network facilitation" theoretical approach can increase both a theoretical and practical understanding of drug use and related risk behaviors. Using the methods of analytic ethnography, it identifies, descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…However, qualitative research among smokers in disadvantaged communities in Glasgow found that social networks and social stressors combined to reinforce smoking patterns, not reduce them (Stead et al 2001). Noninjecting heroin users in San Antonio, Texas, had widely varying patterns of risk behavior based on their membership in familial or peer networks (Valdez, Neaigus, and Kaplan, 2008).…”
Section: Content Composition and Contextmentioning
confidence: 99%
“…However, qualitative research among smokers in disadvantaged communities in Glasgow found that social networks and social stressors combined to reinforce smoking patterns, not reduce them (Stead et al 2001). Noninjecting heroin users in San Antonio, Texas, had widely varying patterns of risk behavior based on their membership in familial or peer networks (Valdez, Neaigus, and Kaplan, 2008).…”
Section: Content Composition and Contextmentioning
confidence: 99%
“…Socio-cultural factors associated with STI acquisition risk among Latinos include familismo (strong identification and attachment to nuclear and extended family), level of acculturation, and traditional gender sex roles [15][16][17][18]. Gender differences in sexual attitudes and behaviors have been documents in Latino adults and youths [19,20].…”
Section: Introductionmentioning
confidence: 96%
“…Valdez et al (2008) studied a special homeless population, Mexican-American non-injecting heroin users, and found that although family networks generated strong social ties, they reduced risky behaviors among the homeless only when those behaviors violated family norms and values. When older family members, such as parents and/or grandparents, engaged in drug use, younger family members, such as siblings, were much more likely to adopt their behaviors.…”
mentioning
confidence: 99%
“…Building on the foundation of past research, current studies have proceeded to investigate factors that influence the mental and physical health of the homeless (La Gory, Fitzpatrick, & Ritchey, 2001) and on special populations among the homeless, such as adolescents (Bao, Whitbeck, & Hoyt, 2000;Dachner & Tarasuk, 2002;Johnson, Whitbeck, & Hoyt, 2005), those with substance abuse problems (Valdez, Neaigus, & Kaplan, 2008;Zlotnick, Tam, & Robertson, 2003), or those that engage in risky sexual behavior Tucker et al, 2009;Tyler, 2007). Other recent studies of the homeless have combined the positive features of both quantitative and qualitative methods (Dordick, 2002;Molina, 2000;Morrell-Bellai, Goering, & Boydell, 2000) and an applied longitudinal research design to explore factors that facilitate exiting homelessness (MacKnee & Mervyn, 2002;Patterson & Tweed, 2009;Toohey, Shinn, & Weitzman, 2004).…”
mentioning
confidence: 99%